Kedudukan Pengemban Jabatan Legal Officer dalam Menjamin Aktivitas Suatu Perseroan Terbatas - I Made Yuda Suarmagita; Ni Luh Mahendrawati; I Gusti Ketut Sri Astiti (Jurnal Analogi Hukum, 2021)
A legal officer is a profession whose job is to take care of all documents, permits, and legal issues that occur within the company. This thesis raises problem formulations, namely How do you assume a legal officer position in guaranteeing the activities of a limited liability company?. How do you assume a legal officer position in guaranteeing the activities of a limited liability company? The research method used is Juridical-Normative. The research used by the author is a statutory approach, a conceptual approach, a case approach, an analytical approach, and a philosophical approach. The technique used is document study or literature study. The results of this study indicate that the position of the Legal Officer in the company is directly under the Board of Directors, given the function of the Legal officer in running a company to manage company documents which include documents, permits, documents, and legal steps that must be taken. taken if there are legal problems for both civil and criminal matters. The legal officer is also authorized to make adjustments to new regulations issued by the government relating to company operations, so that the legality of the company is still recognized by the government.